Improving Medication Adherence with Two-way Short Message Service Reminders in Sickle Cell Disease and Asthma - Pernell, Brandi M.; DeBaun, Michael R.; Becker, Kathleen; Rodeghier, Mark; Bryant, Valencia; Cronin, Robert M. (Applied Clinical Informatics, 2017)
Introduction: Sickle cell disease (SCD) is a childhood and adult disease that primarily affects African Americans, characterized by life threatening sequelae mitigated by medications. One-way and two-way short message service (SMS) medication reminders have differing efficacy in chronic diseases. There is limited literature about SMS medication reminders in SCD.Objective: The goal of this study was to test the feasibility, defined by recruitment/acceptance, retention/attrition, and technology utilization, of two-way SMS medication reminders in individuals with SCD with and without asthma.Materials and Methods: Participants were randomly allocated to standard care or reminders. Two-way SMS reminders were automated using Research Electronic Data Capture (REDCap) for hydroxyurea, fluticasone, budesonide and montelukast. Adherence was measured using the Morisky Medication Adherence Scale-8 (MMAS-8). Asthma control was assessed using the Childhood and Adult-Asthma Control Tests (ACT). Participants were enrolled 28 to 60 days with a common termination date.Results: The recruitment rate was 95% (47/49) and 82.9% completed the study. Among the 47 study participants enrolled, 51.1% were male, 61.7% were adults, median age was 20 (range: 3 to 59), and 98% were African Americans. Of the 26 participants receiving messages, 20% responded on over 95% of the days and usage varied with an average response rate of 33%, ranging from 21% to 46%. Medication adherence scores improved significantly in the intervention group (3.42 before, 5.46 after; p=0.002), but not in the control group (3.90 before, 4.75 after; p=0.080). Childhood-ACT scores improved in the intervention group (19.20 before, 24.25 after). Adult-ACT scores within the intervention arm were unchanged (21.0 before, 22.0 after. ACT scores did not improve significantly.Conclusion: This study demonstrated the feasibility for two-way SMS medication reminders to improve medication adherence in a high-risk population where daily medication adherence is critical to health outcomes and quality of life.Citation: Pernell BM, DeBaun MR, Becker K, Rodeghier M, Bryant V, Cronin RM. Improving medication adherence with two-way short message service reminders in sickle cell disease and asthma: A feasibility randomized controlled trial. Appl Clin Inform 2017; 8: 541–559 https://doi.org/10.4338/ACI-2016-12-RA-0203
Keywords: Sickle cell anemia; asthma; medication adherence; short message service; text